Physico-Chemical and Heavy Metal Valences Reduction of Wastewater from The Beverage Industry by Fungi (Penicillium Sp) - Kola Ahmad Lawal; Adeyinka Adekanmi Abideen; Ibraheem Kehinde Lawal; Oluwafemi Akinkunmi Owolabi; Kafayat Funmi Bamidele; Micheal Ajewole Oluwagbemiga (Three E Science Institute, 2022)
This work aimed to characterize beverage wastewater generated in the beverage industry and to assess wastewater treatment plant performance by fungi (Penicillium sp.) and the feasibility of wastewater reuse. Freshly discharged beverage wastewater was collected and analyzed for the physicochemical parameters such as Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Dissolved Solid (TDS), Nitrate, Phosphate, Magnesium, Calcium, Iron, Copper, and Zinc by standard methods. At a 7-day interval, 190ml of the sterilized local dye wastewater was inoculated with Penicillium sp. for two weeks, and the physicochemical parameters were determined. The results observed for raw, bio-treated and removal efficiency showed: BOD (280 mg-1, 255 mg-1 , 108 mg-1 and 19.64 %, 61.43 %); COD (540 mg-1, 420 mg-1, 285 mg-1 and 43.75%, 88.13%); Nitrate (130 mg-1, 90 mg-1, 25 mg-1 and 30.77%, 80.77%); Phosphate (48 mg-1, 25 mg-1, 5 mg-1 and 30.91%, 78.18%); Calcium (55 mg-1, 38 mg-1, 12 mg-1 and 30.91%, 78.18%); Iron (29 mg-1, 18 mg-1, 07 mg-1 and 37.93 %, 75.86 %); Copper (0.09 mg-1, 0.07 mg-1, 0.02 mg-1 and 22.22 %, 77.78 %); Zinc (0.08, 0.06, 0.03 mg-1 and 22.5%). Fungi (Penicillium sp.) demonstrated the ability to remove pollutants and other wastes from beverage wastewater. These results indicate that some companies employing treatment methods for their effluents do not remove the parameters and heavy metals.